Perceptions of Life Among Women After Hysterectomy in Kandy District Sri Lanka - Abeyrathna, N.P.; Jayasundara, J.M.N.P.; Peramuna, P.G.U.P.K.; Mapa, M.H.M.M.P.; Kumari, L.Y.S.S.; Siriwardhana, E.W.A.I.M. (My University, 2021)
Introduction: Hysterectomy remains as the most commonly performed gynecological surgery in the world. It is a stressful and unpleasant experience for women which can critically influence on their physical, psychological and sexual life. Objective: To explore the experiences of patients who had hysterectomy in Teaching Hospital, Kandy. Methods: In this quantitative descriptive study, 192 women who had hysterectomy during the year 2000 to 2018 at the Teaching Hospital, Kandy were conveniently recruited. Data were collected over the phone using a validated interviewer-administered questionnaire. Ethical approval was obtained from the same hospital. Data were analyzed by descriptive statistics using SPSS 22 version. Results: About two thirds of the participants (118) were belonged to the 41-50 years age category and 75% of the study participants were married. About half of the participants (102) knew very little or merely not known about hormonal therapies. Around 60% of the women indicated that their body weight dramatically increased after the surgery and 30% reported that it took 1-4 months to commence day to day activities after hysterectomy. Majority (about 90%) believed that a womb is needed for the completeness of a woman, and they are worrying about the loss of the womb. Among the participants, approximately one fourth expressed their displeasure of the inability of having children hereafter. About 78% of the participants reported increased vaginal dryness after hysterectomy. Furthermore, about half of them (96) mentioned that more than six months were taken for resume their sexual activities and about 40% reported notable reduction in the number of times of sexual activity after hysterectomy. Conclusions: The presence of psychological and emotional stress was evident in this study. Therefore, exploring patient's experience immediately after hysterectomy can be used to arrange tailored post-operative interventions for the patients to cope with their discomforts thus patients will enable to live a quality life after recovery.

Introduction: Hysterectomy remains as the most commonly performed gynecological surgery in the world. It is a stressful and unpleasant experience for women which can critically influence on their physical, psychological and sexual life. Objective: To explore the experiences of patients who had hysterectomy in Teaching Hospital, Kandy. Methods: In this quantitative descriptive study, 192 women who had hysterectomy during the year 2000 to 2018 at the Teaching Hospital, Kandy were conveniently recruited. Data were collected over the phone using a validated interviewer-administered questionnaire. Ethical approval was obtained from the same hospital. Data were analyzed by descriptive statistics using SPSS 22 version. Results: About two thirds of the participants (118) were belonged to the 41-50 years age category and 75% of the study participants were married. About half of the participants (102) knew very little or merely not known about hormonal therapies. Around 60% of the women indicated that their body weight dramatically increased after the surgery and 30% reported that it took 1-4 months to commence day to day activities after hysterectomy. Majority (about 90%) believed that a womb is needed for the completeness of a woman, and they are worrying about the loss of the womb. Among the participants, approximately one fourth expressed their displeasure of the inability of having children hereafter. About 78% of the participants reported increased vaginal dryness after hysterectomy. Furthermore, about half of them (96) mentioned that more than six months were taken for resume their sexual activities and about 40% reported notable reduction in the number of times of sexual activity after hysterectomy. Conclusions: The presence of psychological and emotional stress was evident in this study. Therefore, exploring patient's experience immediately after hysterectomy can be used to arrange tailored post-operative interventions for the patients to cope with their discomforts thus patients will enable to live a quality life after recovery.

Introduction: Hysterectomy remains as the most commonly performed gynecological surgery in the world. It is a stressful and unpleasant experience for women which can critically influence on their physical, psychological and sexual life. Objective: To explore the experiences of patients who had hysterectomy in Teaching Hospital, Kandy. Methods: In this quantitative descriptive study, 192 women who had hysterectomy during the year 2000 to 2018 at the Teaching Hospital, Kandy were conveniently recruited. Data were collected over the phone using a validated interviewer-administered questionnaire. Ethical approval was obtained from the same hospital. Data were analyzed by descriptive statistics using SPSS 22 version. Results: About two thirds of the participants (118) were belonged to the 41-50 years age category and 75% of the study participants were married. About half of the participants (102) knew very little or merely not known about hormonal therapies. Around 60% of the women indicated that their body weight dramatically increased after the surgery and 30% reported that it took 1-4 months to commence day to day activities after hysterectomy. Majority (about 90%) believed that a womb is needed for the completeness of a woman, and they are worrying about the loss of the womb. Among the participants, approximately one fourth expressed their displeasure of the inability of having children hereafter. About 78% of the participants reported increased vaginal dryness after hysterectomy. Furthermore, about half of them (96) mentioned that more than six months were taken for resume their sexual activities and about 40% reported notable reduction in the number of times of sexual activity after hysterectomy. Conclusions: The presence of psychological and emotional stress was evident in this study. Therefore, exploring patient's experience immediately after hysterectomy can be used to arrange tailored post-operative interventions for the patients to cope with their discomforts thus patients will enable to live a quality life after recovery.
Keywords: Hysterectomy; Physical effects; Psychological disturbances; Sexual impairments